PERANCANGAN KAWASAN WISATA BUDAYA BETAWI DI PULAU LANCANG KECIL, KEPULAUAN SERIBU, D.K.I JAKARTA - Novri Wibisono; Putri Suryandari (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2019)
Indonesia is a country that has the potential of natural and culture resource as well as very interisting history. Located note far form center Jakarta, thousand island have tourist potensial number are very hihg, not only domestic tourist, but foreign tourist. But unfortunately still quit a few people who are aware of the potential of their region. As time gose by, the number of tourist in thousand island is increasing because is located only 25km from downtown Jakarta, one of the place often visited by tourist is Lancang Kecil Island because even tough this island is empty island around the island has the potential still natural, such as clean beaches, mangrove forest, and marine animal around the island. But many existing potential conditions have dissapeared and began to be abandoned by local residence because at this time there are no facilities that support activities to develop the potential, it is hope that with the idea of designing tjis cultural tourism area can become one solutions to further optimize existing tourism potentials and be able to provide benefits to the surronding community.